Middle Classes in Africa Changing Lives and Conceptual Challenges (Frontiers of Globalization, 2018)
This volume challenges the concept of the 'new African middle class' with new theoretical and empirical insights into the changing lives in Sub-Saharan Africa. Diverse middle classes are on the rise, but models of class based on experiences from other regions of the world cannot be easily transferred to the African continent. Empirical contributions, drawn from a diverse range of contexts, address both African histories of class formation and the political roles of the continent's middle classes, and also examine the important interdependencies that cut across inter-generational, urban-rural and class divides. This thought-provoking book argues emphatically for a revision of common notions of the 'middle class', and for the inclusion of insights 'from the South' into the global debate on class. Middle Classes in Africa will be of interest to students and scholars across a range of disciplines, as well as NGOs and policy makers with an interest in African societies.